Psychological Experiences in Facing the Early Situation of the Covid-19 Pandemic in Adolescents, Adults, and the Elderly - Taufik Achmad Dwi Putro; Subandi; Arum Febriani; Zidnilma Fahmalia Hazrati; Abd. Halim; Chintia Viranda; Fadhil Maliky Islah (Universitas Islam Tribakti Lirboyo Kediri, 2022)
The COVID-19 pandemic that has occurred since the beginning of 2019 has changed various aspects of human life. The rapid spread of the virus has restricted human activities, ranging from economic, educational, to socio-religious activities. This situation is a new thing for humans giving rise to various experiences. This study aimed to understand individual psychological experiences, including thoughts, feelings, attitudes, and perceptions in facing the pandemic in various age groups. This research consisted of two stages: the grounded theory survey approach and the phenomenological approach. In the first stage, as many as 447 participants of adolescence and early, middle to late adulthood have filled out an online questionnaire via the google form. The next stage was interviews with 15 participants related to experiences in dealing with the COVID-19 pandemic. The interview results were then analyzed using the Interpretative Phenomenological Analysis method. The results showed that most adolescents described the COVID-19 pandemic as a crisis, while most of the adult group described it with negative emotions. All age groups decided on health as their main concern. Most of the participants considered that there were things to be grateful for during the COVID-19 pandemic. Groups of adolescents and early and middle adults made their family the thing they were most grateful for during the COVID-19 pandemic. Meanwhile, the late adult group placed health as most grateful for. Gratitude was also believed to be a provision for someone to survive and see the positive side of an unpleasant event.